Chronically elevated contact stress exposure correlates with intra‐articular cartilage degeneration in patients with concurrent acetabular dysplasia and femoroacetabular impingement. Issue 11 (6th February 2022) - Aitken, Holly D.; Westermann, Robert W.; Bartschat, Nicholas I.; Meyer, Alex M.; Brouillette, Marc J.; Glass, Natalie A.; Clohisy, John C.; Willey, Michael C.; Goetz, Jessica E.
Abstract: Hip dysplasia is known to lead to premature osteoarthritis. Computational models of joint mechanics have documented elevated contact stresses in dysplastic hips, but elevated stress has not been directly associated with regional cartilage degeneration. The purpose of this study was to determine if a relationship exists between elevated contact stress and intra‐articular cartilage damage in patients with symptomatic dysplasia and femoroacetabular impingement. Discrete element analysis was used to compute hip contact stresses during the stance phase of walking gait for 15 patients diagnosed with acetabular dysplasia and femoral head‐neck offset deformity. Contact stresses were summed over the duration of the walking gait cycle and then scaled by patient age to obtain a measure of chronic cartilage contact stress exposure. Linear regression analysis was used to evaluate the relationship between contact stress exposure and cartilage damage in each of six acetabular subregions that had been evaluated arthroscopically for cartilage damage at the time of surgical intervention. A significant correlation ( R 2  = 0.423, p  < 0.001) was identified between chondromalacia grade and chronic stress‐time exposure above both a 1 MPa damage threshold and a 2 MPa‐years accumulated damage threshold. Furthermore, an over‐exposure threshold of 15% regional contact area exceeding the 1 and 2 MPa‐years threshold values resulted in correct identification of cartilage damage in 83.3% (55/66) of the acetabular subregions loaded during gait. These results suggest corrective surgery to alleviate impingement and reduce chronic contact stress exposures below these damage‐inducing thresholds could mitigate further cartilage damage in patients with hip dysplasia.